Membangun Keterampilan Berbahasa Terstruktur dan Produktif yang Membangun Pikiran dalam Pembelajaran - Khairul Huda (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
In general, language skills developed in the world of education have not been able to increase learning productivity and build students' minds. The purpose of writing this article is to see how to build well-structured speaking skills and how to use language or discussion productively in learning. The writing of this article uses a qualitative descriptive approach. The type of research used is library research or (Library Research), namely by collecting library data relevant to this article. The primary source for writing this article is David D. Preiss and Robert J. Sternberg's book entitled "Innovations in Educational Psychology: Perspectives on Learning, Teaching, and Human Development", while secondary sources are books, articles, and other documents relevant to the theme. research. The results of this study indicate that there are at least three models of approaches that can be developed to improve structured speaking skills and how to use productive language in learning. 1) Deliberative democracy, 2) Discursive class, and 3) Accountable discussion. So it cannot be denied that the interaction in learning with the three models has the capacity to construct or build the minds of students